Cost‐effectiveness and financial risks associated with immune checkpoint inhibitor therapy. Issue 9 (18th June 2020) - Kim, Hansoo; Liew, Danny; Goodall, Stephen
Abstract : The reimbursement of immune checkpoint inhibitors is challenging. Funding these technologies involves the careful balance between awarding innovation and ensuring affordability as increases in drug spending compete directly with other health care and social expenditure. This narrative review examines the recommendations of 2 health technology assessment agencies—the Australian Pharmaceutical Benefits Advisory Committee and the British National Institute of Clinical Excellence—to determine the factors that contribute to the approval and rejection of immune checkpoint inhibitors as well as the use of manage entry schemes and risk management strategies to control expenditure. Reimbursement decisions from 6 immune checkpoint inhibitor drugs (ipilimumab, pembrolizumab, nivolumab, durvalumab, atezolizumab, avelumab ) covering 10 different cancers were examined. The extrapolation of survival beyond the clinical trial and lack of head‐to‐head evidence are some of the main issues relating to cost effectiveness. Payers managed financial risks using different mechanisms such as risk share agreements and financial caps. This review of the reimbursement decisions and subsequent financial impact in Australia and the UK suggests budgets for immune checkpoint inhibitor therapy have been well managed so far. Through risk agreements and managed entry programmes, the example of immune checkpoint inhibitor therapies illustrates that industry and payers can effectively collaborate to ensure that innovative, but expensive, drugs can be made readily available to patients.